Efficacy of the Rho-kinase Inhibitor Ripasudil for Fuchs’ Endothelial Corneal Dystrophy - Fujimoto, Hisataka; Kiryu, Junichi (Journal of Ophthalmology and Research, 2021)
This study aimed to investigate the efficacy of the rho-kinase (ROCK) inhibitor ripasudil administered as ophthalmic solutions for chronic visual acuity impairment induced by Fuchs’ endothelial corneal dystrophy (FECD). Twelve patients with FECD and glaucoma (20 eyes) treated with eye drops (0.4% ripasudil) twice a day were investigated. The control group comprised 12 patients with FECD only (i.e., without glaucoma) (20 eyes). Ripasudil was used during the 18 months of the observation period. All participants had grade 6 dystrophy according to the modified Krachmer grading scale. The mean logMAR visual acuity was improved at 3, 6, 12, and 18 months after ripasudil administration. LogMAR changes 18 months after administration were 0.181 ± 0.170 in the ripasudil group and were significantly superior (P = 9.5 × 10−4) to those in the control group (−0.057 ± 0.106). Central corneal thickness (CCT) 18 months after ripasudil administration/CCT before administration were 0.945 ± 0.029 in the ripasudil group and significantly superior (P = 2.4 × 10−7) compared with those in the control group (1.040 ± 0.032). ROCK inhibitors can be effective against visual acuity impairment and corneal edema in FECD. They can be more effective when administered during the waiting period before corneal endothelium transplantation.